The capability of organic matter decomposition and nutrient uptake in coastal waters of Ca Na bay, Ninh Thuan province - Du, Hoang Trung; Hieu, Nguyen Trinh Duc (Vietnam Journal of Marine Science and Technology, 2019)
This paper focuses on the capability of organic matter decomposition and inorganic nutrient uptake in the coastal waters of Ca Na bay (Ninh Thuan province) in October, 2018 (the rainy season) and May, 2019 (the dry season). The results of laboratory experiments on organic decomposition, photosynthesis and nutrient uptake showed that the BODgh and the average values of k- decay rate in coastal waters of the surveyed area are higher in the rainy season compared with the dry season, with the average BODgh values of 5.474 mgO2/l and 4.768 mgO2/l respectively, and the corresponding k-values of 0.183 day-1 and 0.143 day-1. Howver, the half-life decay of organic matter is lower in the rainy season than in the dry season, with the corresponding values of 5.110 days and 5.571 days. In the studied area, the photosynthesis of phytoplankton strongly absorbs nitrate (NO3-), followed by ammonium (NH4+) and phosphate (PO43-). The capability of nutrient uptake for nitrogen and phosphorus components was 9.17 mgN/m3/hour and 0.92 mgP/m3/hour, respectively in the dry season; and 7.31 mgN/m3/hour and 0.63 mgP/m3/hour in the rainy season. The results of the study are favorable condition for calculating the environmental capacity in the coastal waters of Ca Na bay in the future.